Interaksi Simbolik dalam Perencanaan Komunikasi Pemasaran PT. WOW Komunindo (Studi Etnografi pada Produk Marcopolo) - Nisrina Rahmanita; Muhammad Adi Pribadi (Prologia, 2019)
Marketing communication planning is carried out in order to increase sales and introduce the brand of a product to the audience by conveying effective messages and in accordance with the target audience. PT. Wow Komunindo is one of the advertising companies in Indonesia that carries out marketing communications to meet the wishes of its clients. PT. Wow Komunindo has its own way of planning marketing communications. The role of symbolic interaction and organizational culture is very important in the planning of PT marketing communications. Wow Komunindo. This research uses a qualitative approach with ethnographic methods. Data collection applied was by participant observation, in-depth interviews with employees of PT. Wow Komunindo, as well as document analysis. The conclusion of this study is that there are 6 stages of marketing communication planning which consists of Briefing, Brainstorming, Pre-Production Meeting, Production, Post Production Meeting, and Media Placement. From these stages, interactions occur that contain symbols such as rules, expectations, and organizational culture such as duty rituals and social rituals are created.Perencanaan komunikasi pemasaran dilaksanakan agar meningkatkan penjualan serta memperkenalkan merek sebuah produk kepada khalayak dengan cara menyampaikan pesan yang efektif dan sesuai dengan target audience. PT. Wow Komunindo adalah salah satu perusahaan periklanan di Indonesia yang melakukan komunikasi pemasaran untuk memenuhi keinginan klien. PT. Wow Komunindo mempunyai caranya sendiri dalam merencanakan komunikasi pemasaran. Peran interaksi simbolik serta budaya organisasi sangat lah penting dalam perencanaan komunikasi pemasaran PT. Wow Komunindo. Penelitian ini menggunakan pendekatan kualitatif dengan metode etnografi. Pengumpulan data yang diterapkan adalah dengan observasi partisipan, wawancara mendalam dengan karyawan PT. Wow Komunindo, serta analisis dokumen. Kesimpulan dari penelitian ini yaitu terdapat 6 tahapan perencanaan komunikasi pemasaran yang terdiri dari Briefing, Brainstorming, Pre-Production Meeting, Production, Post Production Meeting, dan Media Placement. Dari tahapan-tahapan tersebut terjadi interaksi yang mengandung simbol-simbol seperti peraturan, harapan, dan juga tercipta budaya organisasi seperti ritual tugas maupun ritual sosial.